ANALISIS STRATEGI KOMUNIKASI PEMASARAN BAND INDIE"MATTED TAPES" DALAM MEMPROMOSIKAN KARYA MUSIK MELALUI INSTAGRAM @BILBOARD_INA - Andhika Putra Anggraito, (2023)
2019 is the year that musicians in Indonesia have written memorable stories for music lovers in the country. The development of Indonesian music and integrated marketing communication strategies is inseparable from the rapid development of technology that has entered Indonesia in large numbers. Hence, researchers are interested in formulating problems related to the marketing communication strategy of the indie band Mattes Tapes marketing their music. Billboard Indonesia, which provides space for indie musicians to promote their work, is the focus of this research. Based on its formulation, this study aims to determine the marketing communication strategy for promotional activities through the Instagram @billboard_ina media so that actors in the music industry can choose media to promote their work. This study uses a qualitative method with in-depth interviews as a data collection technique, and the Miles and Huberman model is used as a data analysis technique. The results of this study indicate that the marketing communication strategy of the indie band Matted Tapes is focused on one type of strategy, namely social media marketing. Matted Tapes only uses one social media to carry out promotional activities. Based on the results of this study, the advantage of the marketing communication strategy carried out by Matted Tapes is to utilize the media as a target market which in this case focuses on young people. The drawback of the Matted Tapes marketing communication strategy is the selection of social media that only makes a little outreach from promotional activities and posting content - the latest content on @billboard_ina, which makes content related to Matted Tapes buried.